Design, fabrication, characterisation and application of nanoelectrode arrays - Compton, R; Wildgoose, G; Rees, N; Streeter, I; Baron, R (2008)
This Letter highlights recent work carried out in our laboratory on methods of fabricating and characterising arrays of nanoelectrodes. We review the template fabrication of random arrays of nanoband electrodes on highly ordered graphite surfaces and on carbon nanotubes, acoustic methods of fabricating random arrays of metal nanoparticles on electrode surfaces, and numerical methods of simulating and modelling the electrochemical processes that occur at such arrays. Finally, examples of electroanalytical applications of nanoelectrode arrays are given, including multi-metal nanoparticle arrays for combinatorial electrochemistry. © 2008 Elsevier B.V. All rights reserved.